2005
DOI: 10.1007/s00418-005-0123-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase in human salivary glands

Abstract: The distribution of the three nitric oxide synthase (NOS) isoforms was determined immunohistochemically in the human minor and major salivary glands with comparison to that of rat salivary glands. In contrast to rat glands, which contained a dense plexus of neuronal NOS-immunoreactive nerve fibers, only a minority of the nerve fibers in human glands showed neuronal NOS immunoreactivity. Human labial and submandibular glands contained sparse NOS-immunoreactive fibers, while only occasional nerve fibers in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…In the human MGl (Soinila et al 2006), nerve endings immunoreactive to VIP, GAL or NPY supplying the mucous acini have been found to be significantly more numerous than those apposing the serous acini. Furthermore, Del Fiacco et al (2014) have revealed that besides VIP-positive axons, also PHM-immunoreactive nerve terminals found in close proximity to acini and ducts are relatively abundant in the human MGl.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the human MGl (Soinila et al 2006), nerve endings immunoreactive to VIP, GAL or NPY supplying the mucous acini have been found to be significantly more numerous than those apposing the serous acini. Furthermore, Del Fiacco et al (2014) have revealed that besides VIP-positive axons, also PHM-immunoreactive nerve terminals found in close proximity to acini and ducts are relatively abundant in the human MGl.…”
Section: Discussionmentioning
confidence: 97%
“…Immunoreactivity to nNOS has been found in a few nerve fibres supplying human, rat, cat and ferret salivary glands (Lohinai et al 1995;Alm et al 1997;Takai et al 1999;Soinila et al 2006). In the ferret and rat, NOS-positive varicose nerve terminals encircled the glandular acini and arteries of various sizes (Alm et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, immunohistochemical analyses of human minor and major salivary glands revealed that nNOS is strongly restricted to the non-neuronal duct epithelium and only a minority of the major salivary gland nerve fibers (surrounding acini, tubuli, ducts and blood vessels) expressed nNOS (Soinila, Nuorva, and Soinila 2006). In addition, salivary gland acinar cells have been demonstrated to express NOS (Looms et al 2002, ;Looms et al 2000, ;Soinila, Nuorva, and Soinila 2006). Human labial salivary gland acinar cells possess NOS activity and exhibit a very low level of NO production without stimulation in vitro (Looms et al 2000).…”
Section: Sources Of No In Human Salivary Glandsmentioning
confidence: 99%